AI-Human Synergy: Transforming the Future of Financial Audit - Naganarendar Chitturi (Journal of information systems engineering & management, 2025)
The integration of artificial intelligence technologies to human auditor skills is a revolutionary change redefining contemporary financial audit practice. Conventional audit approaches, traditionally relying on sampling methods and interval checks, are becoming increasingly insufficient when dealing with exponentially expanding transactional volumes and globally interdependent financial systems. Artificial intelligence systems show remarkable expertise in formal, routine tasks that encompass most audit work, with particularly strong performance in data gathering, pattern analysis, and transactions processing. Human auditors provide invaluable cognitive skills such as professional judgment, situational interpretation, and ethical assessment that remain outside the capabilities of current technology. The symbiotic integration produces collaborative platforms that tap the efficiency of algorithms while maintaining vital professional control necessary for audit credibility. Modern audit firms that are putting AI-supported methods into practice deliver quantitative gains in audit quality in the form of fewer restatement occurrences, improved anomaly detection, and increased coverage from the antiquated sampling methods to full transactional analysis. Technology integration, though, also brings intricate regulatory, ethical, and professional issues that need systematic responses to counterbalance accountability allocation, algorithmic transparency, and professional skills requirements. The change calls for a delicate balance between technological potential and human judgment to preserve bedrock professional values while improving service quality and stakeholder value.